(untitled) (Research, Society and Development, 2020)
Objective: to investigate the frontal lobe cortical activation of older adults and youngs during an exergame session for postural balance. Methodology: cross-sectional study with 20 individuals (10 older adults and 10 youngs) attended exergaming session. Initially, sociodemographic and clinical assessments were carried out and then, an electroencephalographic (EEG) assessment with Emotiv EPOC® during the execution of Nintendo Wii Fit Penguin slide exergame was done. Eight channels of the frontal region and alfa and beta waves were used for analysis. The EEG data was recorded by Emotiv TestBench and imported into MatLab®. SPSS program, Mann-Whitney test and significance level of p<0.05 were used. Results: the mean age of the older adults group (OAG) was 65.1 ± 4.8 years and in the young group (YG) was 22.4 ± 2.3 years. There were no differences in the cortical activation potential between groups for the alpha (p = 0.058) and beta (p = 0.092) waves. There was a greater magnitude in the potential activation of the alpha wave in both groups. For alpha e beta waves, there was one peak activation in F3 channel (left frontal region) in the YG and a greater amount of activation peaks in the OAG, highlighted in F4 channel (right frontal region). Conclusion: cortical activation potential in frontal lobe related to alpha and beta waves in young and older adults does not differ when playing the exergame for postural balance Penguin slide game.